2018
DOI: 10.1159/000492839
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tyrosine 3-Monooxygenase/Tryptophan 5-Monooxygenase Activation Protein Zeta (YWHAZ) Overcomes Drug Resistance and Tumorigenicity in Ovarian Cancer

Abstract: Background/Aims: Cancer stem-like cells are the main cause of tumor occurrence, progression, and therapeutic resistance. However, the precise signals required for the maintenance of the stem-like traits of these cells in ovarian cancer remain elusive. We have thus worked to elucidate the functional role of Tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ), a gene encoding the 14-3-3ζ protein, in the regulation of multidrug resistance and stem cell-like traits in ovarian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ) was identified in 55.9% of all patients’ combinations from all nine cancer types. This protein is present in high levels in different cancer cells and is associated with tumor cell proliferation, cell invasion and migration, and drug resistance (Nishimura et al, 2013; Hong et al, 2018; Deng et al, 2019). This protein target has prognostic potential, and its overexpression is associated with short OS time in non-squamous-cell lung carcinoma (Deng et al, 2019); its knockdown has suppressed tumorigenesis in ovarian cancer cells (Hong et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ) was identified in 55.9% of all patients’ combinations from all nine cancer types. This protein is present in high levels in different cancer cells and is associated with tumor cell proliferation, cell invasion and migration, and drug resistance (Nishimura et al, 2013; Hong et al, 2018; Deng et al, 2019). This protein target has prognostic potential, and its overexpression is associated with short OS time in non-squamous-cell lung carcinoma (Deng et al, 2019); its knockdown has suppressed tumorigenesis in ovarian cancer cells (Hong et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have established a strong relationship between 14 and 3-3 proteins and various cancer types, 48−50 but cysteine modification-related functions have been unclear. However, the 14-3-3 family has emerged as a promising therapeutic target for cancer and neurodegenerative diseases, 51,52 and, therefore, Cys25 and Cys94 of 14-3-3 protein zeta need to be investigated. Peroxiredoxin-1 also plays an important role in cancer development and inflammation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Many previous studies have established a strong relationship between 14 and 3-3 proteins and various cancer types, but cysteine modification-related functions have been unclear. However, the 14-3-3 family has emerged as a promising therapeutic target for cancer and neurodegenerative diseases, , and, therefore, Cys25 and Cys94 of 14-3-3 protein zeta need to be investigated. Peroxiredoxin-1 also plays an important role in cancer development and inflammation. It is a dual-function protein that acts as both an antioxidant enzyme and molecular chaperone. , Peroxiredoxin-1 has been reported to interact with essential signaling molecules such as p53, NF-κB, and Toll-like receptor 4 (TLR4) .…”
Section: Resultsmentioning
confidence: 99%
“…They observed that the knockdown of YWHAZ inhibits cell proliferation, migration, and invasion of gastric cancer cells [44] As Hong et al observed, the YWHAZ downregulation of YWHAZ inhibited cell cycle progression, migration, and the expression of stem cell markers. Moreover, tumorigenicity was suppressed in tumor-bearing BALB/c nude mice following the YWHAZ knockdown [45].…”
Section: Discussionmentioning
confidence: 99%